The Dynamics of Linkages between the Polish Stock Market and Those of the Czech Republic and Hungary as Well as Major World Markets - Doman, Małgorzata; Doman, Ryszard (Studia Oeconomica Posnaniensia, 2013)
In the paper, we analyze linkages between the Polish stock market and the Czech and Hungarian markets after the EU accession of the corresponding countries. For comparison, we examine linkages between the Polish stock market and developed markets: the European and the US market represented by the indices DAX and S&P 500, espectively. The main questions in the analysis concern the nature, dynamics and strength of the linkages. The dynamics of dependencies is modelled by means of Markov-switching copula models, and the applied measures of the strength of the linkages are dynamic Spearman’s rho and tail dependence coefficients.